Transthoracic Echocardiography of the Neonatal Laboratory Piglet - Schwarz, Stephan; Kalbitz, Miriam; Hummler, Helmut D.; Mendler, Marc R. (Frontiers in Pediatrics, 2019)
Background: Piglets are regularly used in biomedical research. Imaging of their cardiovascular system is challenging. On-site diagnostics of the heart can be realized by transthoracic echocardiography, which appears to vary substantially from pig to piglets. To date, there are few data or studies on the feasibility and quality of measurement of functional echocardiographic parameters in neonatal piglets. Objectives: To study the feasibility of transthoracic echocardiography (TEE) in newborn piglets. Methods: In forty-four anaesthetized and intubated newborn piglets (age 32h (12-44h), weight 1220g (1060-1495g), median (IQR)) transthoracic echocardiography was performed using a point of care ultrasound machine (M-Turbo©, FujiFilm SonoSite BV, Amsterdam, Netherlands) with a standard ultrasound transducer. Results: Using 2D- and M-mode-imaging left and right ventricular structures were accessible to transthoracic echocardiography. Diameters of the interventricular septum, the left ventricle and the posterior wall were measured and ejection fraction and shortening fraction was calculated. Both left and right ventricular outflow tract could be imaged and ventricular filling and systolic function could be evaluated. Furthermore, we were able to assess shunts of fetal circulation, such as patent ductus arteriosus, structure of the heart valves and congenital heart defects including ventricular septal defect can be assessed. Conclusions: In summary, transthoracic echocardiography is an implementable modality for assessment of cardiovascular function in the newborn laboratory piglet.